Seawater intrusion induced cadmium activation via altering its distribution and transformation in paddy soil. (November 2022) - Chi, Wenting; Yang, Yang; Zhang, Ke; Wang, Pei; Du, Yanhong; Li, Xiaomin; Sun, Yan; Liu, Tongxu; Li, Fangbai
Abstract: Seawater intrusion can cause environmental risks to paddy soils around estuaries, but the impacts on the availability of heavy metals are still unclear. River water and sea water were collected along the river of an estuary. A stirred-flow experiment was conducted to examine the Cd desorption behavior in Cd-contaminated paddy soil. While the pH increased with increasing salinity levels, more Cd was released with increasing salinity, suggesting that Cd competition by cations and complexation by anions, but not pH, dominated the release of Cd from soils. Moreover, paddy soil was incubated at different salinities under alternating redox conditions. The availability of Cd, as indicated by the diffusive gradients in thin film (DGT), became relatively high with increasing salinity levels during the initial anaerobic and later aerobic stages. The available Cd fractions substantially decreased under anaerobic condition, and then rapidly increased under aerobic condition. When oxygen was introduced into the system, Cd associated with organic matter and Fe–Mn oxides were released, and oxidative dissolution of Cd sulfides was observed, especially in the high salinity treatment. Seawater intrusion affects biogeochemical cycles and can promote rapid export of NH4 +, Fe 2+, and SO4 2− in paddy soils, especially in soils with high salinity. Our findings demonstrated that the high salinity content in paddy soil significantly enhanced the availability of Cd, especially during the drainage stage. Graphical abstract: Image 1 Highlights: High salinity promotes Cd dissolution from paddy soil. Cd competition and complexation dominated the release of Cd from soils. The pH was elevated with high salinity but the Cd availability increased. The effect of salt on redox process contributed to the remobilization of Cd.